Concentration Level and Arm Muscle Endurance Relationship to Archery Accuracy - Muhammad Fadhil Nurida; Mugiyo Hartono (Universitas Negeri Semarang, 2026)
Archery is an individual sport that requires physical, psychological and skill. In this study, the aim is to determine the relationship between concentration and endurance of the arm muscles to archery accuracy in archery athletes in Boyolali Regency. This study uses a test survey with a correlational approach and a cross sectional or one-time data collection design. The population and sample in this study used 45 samples with a total sampling technique. Data analysis uses a simple correlation test and a multiple correlation test. The results of the study show that it can be concluded that there is a strong relationship between concentration and endurance of arm muscles to archery accuracy in archery athletes in Boyolali Regency with an R square value of 0.581. The higher the concentration and endurance of the arm muscles, the higher the accuracy of the archery. The meaning is that the concentration and endurance of the arm muscles contributed 58.1% to archery accuracy in archery athletes in Boyolali Regency.